The Determination of Company Value: Empirical Study on Manufacturing Companies in Basic and Chemical Industry Sector - Febrina Azzifa Salsabilla; Nursiam Nursiam (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research seeks to evaluate the influence of leverage, profitability, and company size on the valuation of firms in the basic and chemical industries that are listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. This research employs a quantitative approach using secondary data obtained from financial statements published on the IDX, along with information from books, journal articles, and official websites. The population studied comprises all manufacturing companies in the basic and chemical industry sectors listed on the IDX within the specified period. Purposive sampling was applied, yielding a sample of 99 companies. Data analysis techniques used include descriptive statistics and multiple linear regression. The findings of the study suggest that while leverage and profitability do not significantly influence company value, company size does. Furthermore, company value is significantly impacted by the combined effects of leverage, profitability, and company size.